Health professionals' views on maternity care for women with physical disabilities: a qualitative study - Martina König-Bachmann; Christoph Zenzmaier; Barbara Schildberger (BMC, 2019)
Abstract Background During pregnancy, childbirth and puerperium, women receive care from a range of health professionals, particularly midwives. To assess the current situation of maternity care for women with physical disabilities in Austria, this study investigated the perceptions and experiences of health professionals who have provided care for women with disabilities during pregnancy, childbirth and postpartum. Methods The viewpoints of the participating health professionals were evaluated by means of semistructured interviews followed by an inductive qualitative content analysis of the interview transcripts, as proposed by Mayring. Results Four main categories emerged from the inductive content analysis: (i) structural conditions and accessibility, (ii) interprofessional teamwork and cooperation, (iii) action competence, and (iv) diversity-sensitive attitudes. According to the participating health professionals, the structural conditions were frequently not suitable for providing targeted group-oriented care services. Additionally, a shortage of time and staff resources also limited the necessary flexibility of treatment measures in the care of mothers with physical disabilities. The importance of interprofessional teamwork for providing adequate care was highlighted. The health professionals regarded interprofessionalism as an instrument of quality assurance and team meetings as an elementary component of high-quality care. On the other hand, the interviewees perceived a lack of action competence that was attributed to a low number of cases and a corresponding lack of experience and routine. Regarding diversity-sensitive attitudes, it became apparent that the topic of mothers with physical disabilities in care posed challenges to health professionals that influenced their natural handling of the interactions. Conclusion The awareness of one's own attitudes towards diversity, in the perinatal context in particular, influences professional security and sovereignty as well as the quality of care of women with disabilities. There is a need for optimization in the support and care of women with physical disabilities during pregnancy, childbirth and puerperium.